Identifying Indoor Air Quality: Ventilation in Healthcare Facilities Semarang - Savanti, Fisa; Wibowo, Ardiyan Adhi; Pratiwi, Isna; Putra, Bambang Setyohadi Kuswarna (Universitas Islam Lamongan, 2024)
A building requires good ventilation planning, especially for health facility buildings. Ventilation plays a role in supplying clean air and creating good indoor air quality. This study identifies the air change rate that improves indoor air quality in health facility buildings in tropical areas. Direct field measurements were conducted in this study and then analyzed based on the appropriate recommendation standards. The results of this study show that some variables still need to meet the recommendation standards in meeting the requirements of good air quality. This proves that ventilation has an essential role in air conditioning in the room, creating clean and healthy air. This research provides an overview that ventilation needs to be carefully designed to achieve good air quality, so it is expected to reduce contaminants in the air.